Linking climate change risks and rights of upland peoples in the Mekong - Xu, Jianchu; Daniel, R. (Earthscan, 2011)
This chapter includes the following sections: the risks analysis of geophysical hazards and climate change in the Mekong uplands, accelerated risks and socially constructed vulnerabilities; the value and challenges in a rights-based apprach; the risks-rights nexus towards integrating rights for living with risks; potential strategies and means to cope with, as well as rebound after, climate risks and disasters; discussion and conclusions about improving and incorporating local rights as well as addressing the adaptive capacity of upland peoples to climate change.